Assessment of Lag of Accommodation with Nott Retinoscopy between the Ages of 5 and 19 - León Álvarez, Alejandro (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2014)
Objective: To determine the normal values of lag of accommodation in a population between the ages of 5 and 19 from public schools in Pereira. Materials and methods: Lag of accommodation in 505 individuals (392 individuals selected) from public schools in Pereira was assessed using the Nott retinoscopy. Results: The average lag of the entire group was 0.51 D (percentile 5 = 0.19 D; percentile 95 = 0.89 D); there was no divergence based on gender, but there was divergence between the age groups of 5-9 and 15-19 (Kruskal-Wallis = 0.0214). Conclusions: Lag of accommodation in this group was lower than reported in other studies. Therefore, we recommend using the results found in the assessed ages as benchmarks in our environment.